The Effectiveness of the e-SPM Application in Monitoring Regional Service Performance at the Directorate General of Regional Development, Ministry of Home Affairs - Rafel Lina; Khaerul Umam Noer (Publik : (Jurnal Ilmu Administrasi), 2025)
This study aims to analyze the effectiveness of the e-SPM application in monitoring the performance of regional services at the Directorate General of Regional Development, Ministry of Home Affairs. The e-SPM application was developed as a digital monitoring system to support the implementation of Minimum Service Standards (Standar Pelayanan Minimal/SPM) across regional governments in Indonesia. This study employs a descriptive research design with a qualitative approach to obtain an in-depth understanding of the application’s performance, usability, and contribution to administrative effectiveness. Data were collected through interviews, observations, and document analysis involving administrators and members of the SPM team responsible for managing and monitoring regional service data. The results indicate that the e-SPM application is effective in supporting the monitoring of regional service performance at the provincial, district, and city levels. The application has significantly improved the work efficiency of the SPM team by simplifying data input, accelerating reporting processes, and enabling real-time monitoring of SPM achievement across regions in Indonesia. Furthermore, the system quality, information quality, and service quality of the e-SPM application have generally met user needs, particularly in terms of data accuracy, accessibility, and integration. Administrators perceive the application as helpful in decision-making and performance evaluation related to regional service delivery.However, despite its overall effectiveness, the study also identifies several areas that require continuous improvement, including system responsiveness, user interface optimization, and periodic feature updates to accommodate policy changes and increasing data complexity.